Chondrocytes respond both anabolically and catabolically to impact loading generally considered non-injurious. (March 2021) - Santos, Stephany; Richard, Kelsey; Fisher, Melanie C.; Dealy, Caroline N.; Pierce, David M.
Abstract: We aimed to determine the longitudinal effects of low-energy (generally considered non-injurious) impact loading on (1) chondrocyte proliferation, (2) chondroprogenitor cell activity, and (3) EGFR signaling. In an in vitro study, we assessed 127 full-thickness, cylindrical osteochondral plugs of bovine cartilage undergoing either single, uniaxial unconfined impact loads with energy densities in the range of 1.5–3.2 mJ/mm 3 or no impact (controls). We quantified cell responses at two, 24, 48, and 72 h via immunohistochemical labeling of Ki67, Sox9, and pEGFR antibodies. We compared strain, stress, and impact energy density as predictors for mechanotransductive responses from cells, and fit significant correlations using linear regressions. Our study demonstrates that low-energy mechanical impacts (1.5–3.2 mJ/mm 3 ) generally stimulate time-dependent anabolic responses in the superficial zone of articular cartilage and catabolic responses in the middle and deep zones. We also found that impact energy density is the most consistent predictor of cell responses to low-energy impact loading. These spatial and temporal changes in chondrocyte behavior result directly from low-energy mechanical impacts, revealing a new level of mechanotransductive sensitivity in chondrocytes not previously appreciated. Graphical abstract: Highlights: Low-energy mechanical impacts (1.5–3.2 mJ/mm 3 ) did not induce macroscale damage. Low-energy impacts stimulate time-dependent anabolic and catabolic responses. SZ chondrocytes increased Sox9 labeling with increased impact energy density. MZ and DZ chondrocytes responded catabolically to increased impact energy density. Impact energy density better predicts cell responses vs. engineering strain or stress.